2006
DOI: 10.1183/09031936.06.00002706
|View full text |Cite
|
Sign up to set email alerts
|

Survey ofPseudomonas aeruginosagenotypes in colonised cystic fibrosis patients

Abstract: The current authors aimed to examine whether cystic fibrosis (CF) patients in Belgium shared Pseudomonas aeruginosa genotypes and to compare the genotypes of isolates from the same patients during two consecutive years. A Belgian databank of the P. aeruginosa genotypes of all colonised CF patients was created.Sputum samples from a total of 276 P. aeruginosa colonised patients during 2003, and from a subgroup of 95 patients in 2004, were analysed. Patients were asked about any social contact between each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…A total of 427 environmental samples were obtained and genotyped with a median number of eight samples per patient (mean (range) samples 8.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)). Nurses were asked to collect a minimum of four samples per home, with at least one sample from the kitchen, bathroom, toilet and the patient's nebuliser.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 427 environmental samples were obtained and genotyped with a median number of eight samples per patient (mean (range) samples 8.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)). Nurses were asked to collect a minimum of four samples per home, with at least one sample from the kitchen, bathroom, toilet and the patient's nebuliser.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is designated ERIC2-PCR in the present study. This allowed a reduction in the number of isolates that were subsequently genotyped by the more laborious fluorescent amplified fragment length polymorphism analysis technique [7], since only single representatives of each ERIC2-PCR type were further genotyped by this procedure. Table 1 presents the epidemiological and sampling data of the patients included.…”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not all studies have identified evidence of highly prevalent genotypes. Reports from Belgium, British Columbia (Canada) and New Zealand have only identified small clusters of genetically similar isolates in epidemiologically unrelated patients [22][23][24].…”
Section: Discussionmentioning
confidence: 99%